Pengaruh Variabel Dalam Customer Experience, Service Experience Dan Prestise Terhadap Frekuensi Perjalanan Penumpang - priyanto, sapto; Damayanti, Ajeng Tyas (Politeknik Perkeretaapian Indonesia Madiun, 2020)
PT KA Tourism continues to innovate to attract customers, one of which is by introducing KA Priority. The services offered by Priority KA are specifically intended for passengers who want more comfort during the trip. The interaction of passengers with the services provided is a special experience for passengers. Passenger experience can be felt through personal experience (customer experience) and from the experience of enjoying services while traveling (service experience). Prestige is a separate consideration for passengers in the use of a classy mode such as the Priority Train due to the luxury of the facilities offered. This study aims to determine the effect of variables that shape customer experience and service experience, namely sense, feel, think, act, relate, incentive, accessibility, convenience, utility, environment, benefits, trust and prestige on the frequency of passenger travel. Data collection was carried out by distributing questionnaires to 150 respondents using random sampling techniques. The collected data is then processed using multiple linear regression models. The results showed that variables that influence the frequency of passenger trips are sense, incentive, convenience, environment and prestige